Pengaruh Advertising Web Series â€œEmina Beauty Bestieâ€ Terhadap Minat Beli Konsumen Emina - Anesti Dila Ariyatman; Heppy Millanyani (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Internet users are getting higher, affecting the marketing strategy undertaken. One of them is the emergence of web series advertising as the innovation for a product marketing strategy. During intense competition between companies, Emina launched a web series that aired on YouTube with the title â€œBeauty Bestieâ€ to stay afloat. This research was conducted to determine the effect of Emina's advertising web series on consumer purchase intention. So that it can provide input for companies in terms of increasing purchase intention, and whether this web series-type advertising strategy needs to be continued or not. The research was conducted by distributing questionnaires to 385 respondents through Google Forms, with the population is those who have seen the web series entitled "Emina Beauty Bestie" on YouTube. The results showed that consumer perceptions of advertising and purchase intention in the very good category. The results of the coefficient of determination show that the advertising variable has an effect of 29.3% on purchase intention. Based on multiple regression analysis showed that the dimensions of the advertisement were the most influential factor. Based on the research results, Emina is expected to be able to use language that can persuade consumers' interest in making web series. For further researchers, it is recommended to expand this research with different variables. Keywords: Marketing, Advertising, Web Series, Youtube, Purchase Intention